The Association between Birth Weight and Gestational Age and Asthma in 6-7- and 13-14-Year-Old Children - Zamani Raheleh; Alikhani Ahmad; Heydarzadeh Abtin; Zare Roghaye; Hashemain Sara; Rahimi Siavash (Scientifica)
Background. Previous studies that assessed the role of birth weight and gestational age in the risk of asthma have been conflicting. Objectives. To examine the association between birth weight and gestational age and symptoms of asthma. Patients and Methods. Subjects were 6656 school children of ages 6-7 and 13-14 years from urban districts of Mazandaran, Iran. ISAAC questionnaires were used. Results. There was an increased risk of “wheeze ever” in both age groups with birth weight under 2.5 kg and in all subgroups of low birth weight (LBW). Birth weight more than 3.5 kg was associated with lower risk of “severe asthma” in age group 6-7 years. With respect to gestational age, higher risks of “wheeze ever,” “asthma ever,” and “night cough in the past 12 months” were found in age group 13-14 years born before 37 weeks and the risk of “severe asthma” was higher in younger group (6-7 years). A lower risk of "asthma ever" was also found in 6-7-year-old children and 13-14-year-old girls who were born after 40 weeks. Conclusions. This study showed that there is a direct relation between “wheeze ever” and LBW and an inverse relation between risk of “severe asthma” and birth weight more than 3.5 kg.